2002
DOI: 10.1097/00007890-200209150-00013
|View full text |Cite
|
Sign up to set email alerts
|

Long-term renal function in kidneys from non-heart-beating donors: A single-center experience1

Abstract: Our results for NHBD renal transplants confirm that such grafts suffer primary warm ischemic injury, shown by the increased incidence of acute tubular necrosis and consequent delayed graft function. This produced poor renal function at the time of hospital discharge. After 3 months, the renal function of NHBD cases improved to the level seen in HBD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
43
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 18 publications
4
43
1
Order By: Relevance
“…This contrasts with other studies which have shown a negative impact of DGF on kidney allograft survival from SCD donors (11)(12)(13)(14)(15)(16). DGF is a multifactorial phenomena resulting from warm and cold ischemia, poor donor quality and/or early rejection (16).…”
Section: Discussioncontrasting
confidence: 94%
“…This contrasts with other studies which have shown a negative impact of DGF on kidney allograft survival from SCD donors (11)(12)(13)(14)(15)(16). DGF is a multifactorial phenomena resulting from warm and cold ischemia, poor donor quality and/or early rejection (16).…”
Section: Discussioncontrasting
confidence: 94%
“…21 Liberal use of DCD kidneys may lead to considerable expansion of the donor pool but is associated with a relatively high incidence of delayed graft function and primary nonfunction. [12][13][14][15][16][17][18]22,23 In this study, graft failure in the first 3 months after transplantation was twice as likely for DCD kidneys than for CLINICAL EPIDEMIOLOGY www.jasn.org DBD kidneys; however, DCD kidneys that overcome the early posttransplantation period function as long as DBD kidneys [12][13][14][15][16][17][18] ; therefore, it is unclear whether dialysis patients who are on the waiting list should accept an offer for DCD kidney transplantation or continue dialysis treatment until a conventional DBD kidney is available.…”
Section: Discussionmentioning
confidence: 80%
“…As a consequence, the incidence of delayed graft function and primary nonfunction in DCD kidney transplantation is relatively high, although survival of functioning grafts seems to be satisfactory. [12][13][14][15][16][17][18] During the past decade, DCD has evolved into routine clinical practice that currently supplies Ͼ10% of all deceased-donor kidneys in the United States and up to 50% in the Netherlands; however, it is unknown whether patients who receive a DCD kidney live longer than patients who receive conventional therapy (i.e., continue dialysis treatment with the option of later receiving a DBD kidney). We therefore evaluated the effect of kidney transplantation from different types of deceased donors on the survival of dialysis patients who were on the waiting list in an observational cohort study including all patients who were registered on the Dutch waiting list for a first kidney transplantation between 1999 and 2004.…”
mentioning
confidence: 99%
“…However, the value of machine perfusion parameters to predict PNF is relatively unknown, as the incidence of PNF after transplantation is generally low. DGF, as an alternative outcome measure, is less useful because DGF does not affect long-term survival in DCD kidneys (4)(5)(6)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%